Experimental design for discrepant models: selecting mechanistic models of IKr through informative experiments - Shuttleworth, Joseph George (2025)
In cardiac electrophysiology applications, mathematical models are relied upon to provide quantitatively accurate predictions. The potassium current IKr is of particular importance because its blockage by drugs is known to cause dangerous changes in heart rhythm. To help quantify the risk presented by potential new drugs, we require mathematical models which produce quantitatively accurate predictions and accurately describe the gating behaviour of a cell’s ion channels (particularly those which carry IKr). Building such models requires experimental data that allows both the selection of appropriate model structures and the inference of model parameters. Recently, short “information-rich” experimental designs have been developed, allowing cell-specific models to be fitted. Here, new experimental designs can be specified, which allow the collection of new data under previously unseen IKr dynamics. The resulting data promise to improve models of the gating dynamics of IKr, improve our understanding of cardiac electrophysiology as a whole, and improve the risk-classification of new drugs.